Hecke-Clifford Algebras and Spin Hecke Algebras IV: Odd Double Affine Type - Khongsap, T.; Wang, W. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We introduce an odd double affine Hecke algebra (DaHa) generated by a classical Weyl group W and two skew-polynomial subalgebras of anticommuting generators. This algebra is shown to be Morita equivalent to another new DaHa which are generated by W and two polynomial-Clifford subalgebras. There is yet a third algebra containing a spin Weyl group algebra which is Morita (super)equivalent to the above two algebras. We establish the PBW properties and construct Verma-type representations via Dunkl operators for these algebras.